IUTAM Symposium on Computational Physics and New Perspectives in Turbulence Proceedings of the IUTAM Symposium on Computational Physics and New Perspectives in Turbulence, Nagoya University, Nagoya, Japan, September, 11-14, 2006 - Kaneda, Yukio (IUTAM Bookseries, 2008)
Turbulence remains one of the most challenging problems in classical physics. The papers collected in this volume are the proceedings of an IUTAM S- posium on turbulence, entitled Computational Physics and New Perspectives in Turbulence. The symposium was held in September 2006, at Nagoya U- versity in Japan. The last few years have witnessed a rapid and dramatic rise in our ability to compute highly complex physical systems. As in other ?elds, this has had a major impact on the way in which we approach the problem of turbulence, opening up a new phase of research by providing an opportunity to study the nature of fully-developed turbulence in unprecedented detail. Leading experts in turbulence were brought together at this Symposium to exchange ideas and discuss, in the light of the recent progress in computational methods, new perspectives in our understanding of turbulence. The Symposium also fostered a vigorous interaction between those who pursue computations, and those concerned with developments in experiment and theory. There were 104 participants representing 13 countries, and the presen- tionsandconsequentdebateextendedoveraperiodoffourdays.Throughout, emphasis was placed on the fundamental physical interpretation of turbulent phenomenon. The topics covered included: (i) computational physics and the theoryofcanonicalturbulent?ows;(ii)experimentalapproachestofundam- tal problems in turbulence; (iii) turbulence modeling and numerical methods; and (iv) geophysical and astrophysical turbulence.